White Blood Cell and Granulocyte Counts Are Independent Predictive Factors for Prognosis of Advanced Pancreatic Caner - Lanyun Feng; Shihui Gu; Peng Wang; Hao Chen; Zhen Chen; Zhiqiang Meng; Luming Liu (Gastroenterology Research and Practice)
Background. Pancreatic cancer is associated with high death rates and limited therapeutic options, with no effective predictive factors being available for prognosis at present. In this study, we evaluate the value of using blood test results for pancreatic cancer prognosis. Method. The records of 214 pancreatic cancer patients were reviewed. Blood test results for white blood cell (WBC), granulocyte, neutrophil, lymphocyte, platelet count, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were dichotomized on the basis of median values. This was followed by univariate and multivariate analyses between groups. Results. Patients with pretreatment values in the range WBC≥5.8×109/L, granulocyte≥3.7×109/L, neutrophil≥3.9×109/L, lymphocyte<1.4×109/L, and NLR≥2.8 showed significant correlations pointing to poorer overall survival. Multivariate analysis indicated that WBC≥5.8×109/L (HR=1.808; 95% CI=1.055–3.096; p=0.031) and granulocyte≥3.7×109/L (HR=7.346; 95% CI = 1.275–42.321; p=0.026) can be taken to be independent prognostic factors for overall survival in pancreatic patients. Conclusion. Pretreatment values of WBC and granulocyte count were independent factors with poor prognosis ability with respect to pancreatic cancer.